2019
DOI: 10.1136/heartjnl-2019-315925
|View full text |Cite
|
Sign up to set email alerts
|

Lifetime cardiovascular management of patients with previous Kawasaki disease

Abstract: Kawasaki disease (KD) is an inflammatory disorder of young children, associated with vasculitis of the coronary arteries with subsequent aneurysm formation in up to one-third of untreated patients. Those who develop aneurysms are at life-long risk of coronary thrombosis or the development of stenotic lesions, which may lead to myocardial ischaemia, infarction or death. The incidence of KD is increasing worldwide, and in more economically developed countries, KD is now the most common cause of acquired heart di… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
66
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 68 publications
(67 citation statements)
references
References 44 publications
0
66
0
1
Order By: Relevance
“…Previous pathological studies in KD patients showed all cardiac tissues are associated with the acute inflammatory phase of the disease. Vasculitis leads to the destruction of normal arterial structure, followed by aneurysm expansion, especially affecting the proximal coronary artery, destruction of intima and media, and replacement of myocytes by fibroblasts and connective tissue (1). The most important complication is serious coronary artery lesions (CAL).…”
Section: Introductionmentioning
confidence: 99%
“…Previous pathological studies in KD patients showed all cardiac tissues are associated with the acute inflammatory phase of the disease. Vasculitis leads to the destruction of normal arterial structure, followed by aneurysm expansion, especially affecting the proximal coronary artery, destruction of intima and media, and replacement of myocytes by fibroblasts and connective tissue (1). The most important complication is serious coronary artery lesions (CAL).…”
Section: Introductionmentioning
confidence: 99%
“…There is consensus that radiation exposure (due to imaging), is associated with an increase in lifetime cancer risk, especially in children and should be kept to a minimum ( 18 , 19 ). Recent guidelines consider this radiation exposure and therefore mention CMR as a good imaging technique in KD ( 6 ), however, our data suggest cCTA is the more preferred modality for the visualization vascular morphology, thrombus formation and calcified lesions. CMR is valuable to visualize tissue characteristics and physiology, and has been used to demonstrate and in particular ischemia and tissue damage following myocardial infarction in KD ( 20 , 21 ).…”
Section: Discussionmentioning
confidence: 77%
“…Invasive CAG is not routinely used because of its invasive nature and risk of complications. In a recent overview, the need for guidance for the long-term management of KD patients was emphasized, suggesting non-invasive modalities such as echocardiography and CMR, and only when other modalities cannot be used, to consider low radiation dose computed tomography (CT) ( 6 ). As the limitations of echocardiography are known, we have been performing additional imaging such as cCTA and CMR, in selected patients in our national referral center ( 7 ).…”
Section: Introductionmentioning
confidence: 99%
“…It is conjectural whether endothelial dysfunction correlates with occurrence of CAAs (123)(124)(125)(126). Patients with KD and CAAs have been reported to have an increased risk of myocardial infarction and early deaths (11,116,(127)(128)(129)(130). Recent literature has, however, suggested that long term cardiovascular morbidity in patients with KD may not only be restricted to patients who have been detected to have CAAs (11,131).…”
Section: Endothelial Dysfunction In Patients With Kdmentioning
confidence: 99%